Evaluation of Trihalomethane Formation Potential Due To Anthropogenic Sources in the Ground Water of Kanpur - Nidhi Dixit Mishra; S. C. Dixit; H. C. Srivastava (E-Journal of Chemistry, 2012)
The ground water of Jajmau(which is the hub of tanneries), Kanpur has been evaluated for trihalomethane formation potential in January and May, 2009.Bromide is absent. Chloroform is the only THM species identified in all the ground water samples. The levels of chloroform are found below the regulated WHO guideline value of 300 μgL-1.THM formation rate is very fast in first 24 h. as compared to that of the exceeding reaction time (>24 h). High TOC content is found in both the winter and summer seasons. Values of THMFP increase as the chlorine doses from 14 mg/L to 17 mg/L increased in both the seasons.